Definition of Reference Vertices using the Terrestrial Methods of Planialtimetric Measurement with Total Station (MTMs) and GNSS Positioning (Research, Society and Development, 2022)
The purpose of this research is to study surveys and procedures for the definition of Reference vertices (or points), or Immediate Support, which are useful for the dimensional building control. This provides a methodology that determines with accuracy the planialtimetric position of reference points, necessary for the three-dimensional and two-dimensional control of buildings; the realization of geodesic structures that define reference point fields can be used later by the local community and public and private agencies for the execution of works that require geospatial information. In this context, the GNSS Relative Static Positioning and Leveling with GNSS technology and the terrestrial methods of planialtimetric measurement with Total Station, Polygonation with forced centering and Trigonometric Leveling with short and long views were applied; in this last case, long views from 250 m are considered. With the investigated methodology, positional accuracies of ±2 to ±4 mm were obtained. The lowest values (highest accuracies) calculated among all the adjustment procedures are obtained by adjusting the network observations by measurements of the classical topographic methods. The 3D Grid or 3D Geodetic Grid adjustment showed the highest accuracy if using only GNSS coordinates and observations from topographic methods (slope distances, horizontal and zenith angles) between vertices of the Polygonation method. With the introduction of GNSS inclined distances the fit results in a higher statistic.